Selenium-dependent metabolism of purines: A selenium-dependent purine hydroxylase and xanthine dehydrogenase were purified from Clostridium purinolyticum and characterized - Self, William T. (The National Academy of Sciences, 2000)
During purification of the selenium-dependent xanthine dehydrogenase (XDH) from Clostridium purinolyticum, another hydroxylase was uncovered that also contained selenium and exhibited similar spectral properties. This enzyme was purified to homogeneity. It uses purine, 2OH-purine, and hypoxanthine as substrates, and based on its substrate specificity, this selenoenzyme is termed purine hydroxylase (PH). The product of hydroxylation of purine by PH is xanthine. A concomitant release of selenium from the enzyme and loss of catalytic activity on treatment with cyanide indicates that selenium is essential for PH activity. Selenium-dependent XDH, also purified from C. purinolyticum, was found to be insensitive to oxygen during purification and to use both potassium ferricyanide and 2,6-dichloroindophenol as electron acceptors. Selenium is required for the xanthine-dependent reduction of 2,6-dichloroindophenol by XDH. Kinetic analyses of both enzymes revealed that xanthine is the preferred substrate for XDH and purine and hypoxanthine are preferred by PH. This characterization of these selenium-requiring hydroxylases involved in the interconversion of purines describes an extension of the pathway for purine fermentation in the purinolytic clostridia.